Additive for lithium slag concrete, preparation method of additive and concrete

By using homemade super dispersants, early strength dispersants, fluidity time-varying dispersants and liquid triterpene saponins in lithium slag concrete, the problems of high admixture dosage, slump loss and too long settling time caused by lithium slag injection into concrete are solved, and the good fluidity and early strength of concrete are achieved.

CN119797804AActive Publication Date: 2025-04-11SICHUAN SHUDAO CONSTR TECH CO LTD

Patent Information

Application Number
CN202510032573.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The incorporation of lithium slag into concrete leads to problems such as high admixture dosage, loss of concrete slump and excessive settling time.

Method used

The homemade superdispersant, homemade early strength dispersant, homemade fluidic time-varying dispersant and liquid triterpene saponin are used, and the combination of these dispersants is added to the concrete containing lithium slag to improve dispersion performance, fluidity and early strength.

Benefits of technology

The amount of lithium slag concrete admixture is reduced, the flowability and ease of concrete is improved, the settling time is shortened, and the requirements of engineering construction are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses an admixture for lithium slag concrete, a preparation method of the admixture and concrete, and the admixture comprises the following components in parts by weight: 80-110 parts of a self-made hyperdispersant and 70-90 parts of a self-made early strength dispersant, the invention relates to an anti-freezing agent which comprises the following components in parts by weight: 40-55 parts of self-made flowable time-varying dispersant, 20-30 parts of unencrypted silica fume, 1.0-1.5 parts of liquid triterpenoid saponin and 700-760 parts of deionized water. The admixture for the lithium slag concrete is doped in concrete mixing, the situation that the mixing amount of the admixture for the lithium slag concrete is not easy to control can be improved, the production difficulty is reduced, the lithium slag concrete can have good flowability and workability, the engineering construction requirements are met, the defect that the setting time of the concrete is too long can be overcome, and the concrete quality is improved. The project progress is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to an admixture for lithium slag concrete, a preparation method thereof and concrete. Background Art

[0002] Lithium has excellent physical and chemical properties, making it an important raw material in new energy batteries and playing a huge role in the field of energy storage. my country is rich in lithium-containing ore resources, mainly spodumene and lepidolite, and the extraction of lithium from lithium ore will produce a large amount of lithium slag. Taking spodumene as an example, the production of 1 ton of battery-grade lithium carbonate produces about 8-10 tons of lithium slag. At present, the annual output of lithium slag in China is as high as several million tons, which brings great pressure to the ecological environment. How to realize the comprehensive utilization of lithium slag has become particularly important.

[0003] Concrete has been widely used in modern civil engineering due to its low price and excellent performance. Lithium slag has high content of SiO2 and Al2O3 and excellent volcanic activity. It can be used as a mineral admixture for concrete to improve the strength of concrete. However, the following problems arise when lithium slag is used as a concrete admixture:

[0004] (1) Lithium slag powder is loose and porous, and has strong adsorption to concrete mixing water and water reducing agent, which makes it difficult to control the dosage of concrete admixtures. If the dosage of admixtures is too large, the concrete is prone to delayed water bleeding. If the dosage is too small, the concrete cannot be opened, or after the concrete is opened, the loss is too fast, which increases the difficulty of concrete production.

[0005] (2) The microstructure of lithium slag powder is composed of rod-shaped crystals and layered gravel particles. When added to concrete, there is no ball effect, resulting in poor fluidity of the concrete.

[0006] (3) Lithium slag powder contains a large amount of dihydrate gypsum, which causes the concrete to take too long to set, affecting the progress of the concrete project. Summary of the invention

[0007] The purpose of the present invention is to provide an admixture for lithium slag concrete, which is added to concrete containing lithium slag to solve the problems of high admixture dosage, concrete slump loss and long setting time caused by adding lithium slag to concrete.

[0008] In addition, the present invention also provides a method for preparing the admixture and concrete containing the admixture.

[0009] The present invention is achieved through the following technical solutions:

[0010] An admixture for lithium slag concrete comprises the following components in parts by weight:

[0011] 80-110 parts of homemade super dispersant, 70-90 parts of homemade early strength dispersant; 40-55 parts of homemade fluidity time-varying dispersant, 20-30 parts of undensified silica fume, 1.0-1.5 parts of liquid triterpenoid saponin, 700-760 parts of deionized water;

[0012] The self-made hyperdispersant is obtained by using a branched polyether monomer as the base material and simultaneously adding material A and material B to react under the action of an initiator, wherein material A is an acrylic acid aqueous solution; material B is an aqueous solution containing vitamin C and mercaptoethanol;

[0013] Among them, the self-made early strength dispersant is obtained by reacting triethanolamine and ethylene oxide as reaction raw materials under the action of alkaline catalyst;

[0014] Among them, the self-made fluidity time-varying dispersant is obtained by using ethoxy vinyl polyether and hydrophobic sustained-release monomer as base materials, and simultaneously adding C material and D material to react under the action of a strong oxidant; wherein, C material is an aqueous solution containing acrylic acid and hydroxypropyl acrylate, and D material is an aqueous solution containing vitamin C and mercaptopropionic acid.

[0015] The self-made hyperdispersant prepared with branched polyether monomer as base material contains a hyperbranched long side chain comb-shaped molecular structure, which can increase the thickness of the adsorption layer of the dispersant on cement particles and increase the spatial repulsion between cement particles, thereby achieving efficient dispersion performance and reducing the dosage of lithium slag concrete admixture.

[0016] The self-made time-varying fluidity dispersant prepared by using ethoxy vinyl polyether and hydrophobic slow-release monomer as base materials contains a slow-release hydrophobic group, so that the initial conformation of the self-made time-varying fluidity dispersant is curled and the adsorption capacity is weak. Under the action of alkali in concrete slurry, slow hydrolysis occurs, the molecular conformation gradually stretches, the adsorption effect on cement particles is enhanced, and the molecular effect is also enhanced accordingly, so that the fluidity of the concrete can be maintained for a certain period of time.

[0017] The self-made early-strength dispersant prepared by the present invention with triethanolamine and ethylene oxide as reaction raw materials is a star-shaped polymer, which gives full play to the role of short main chain and long side chain, can achieve single-molecule dispersion, and expose more hydration sites, thereby promoting cement hydration, thereby offsetting the slow setting effect caused by excessive dihydrate gypsum, shortening the setting time, and ensuring the progress of engineering construction; the dispersed silicon micropowder has smaller particles and more volcanic ash reaction sites, which can also play an early strength role to a certain extent.

[0018] The present invention introduces liquid triterpenoid saponin, the molecular structure of which contains hydrophilic-hydrophobic groups, and can introduce tiny bubbles into the ready-mixed concrete, thereby exerting a ball effect and making the concrete have good fluidity.

[0019] In summary, the present invention solves the problems of high admixture dosage, concrete slump loss and long setting time caused by adding lithium slag into concrete by adding a homemade super dispersant, a homemade early strength dispersant, a homemade fluidity time-varying dispersant and liquid triterpenoid saponin to concrete containing lithium slag.

[0020] In a preferred embodiment, the preparation process of the self-made hyperdispersant comprises the following steps:

[0021] S1. Add a basic catalyst to 50-80 parts of hydroxybutyl vinyl ether, heat to 100-120° C. under a nitrogen environment, introduce 980-1020 parts of ethylene oxide within 90-120 minutes, and react for 30-45 minutes; add 31-50 parts of glycidol, react for 3-6 minutes, continuously introduce 450-500 parts of ethylene oxide within 120-150 minutes, react for 60-80 minutes, cool to 60° C., and add 1000-1100 parts of deionized water; obtain a branched polyether monomer solution;

[0022] S2. Add 50-70 parts of deionized water to 200-220 parts of branched polyether monomer solution, and control the temperature to 12-15° C.; add initiator and stir for 5-10 minutes, then drop material A and material B at the same time, react for 30-40 minutes, and obtain a self-made hyperdispersant.

[0023] In a preferred embodiment, in step S1, the alkaline catalyst includes KOH; in step S2, the dropwise addition time of material A is 30 min to 40 min, and the dropwise addition time of material B is 35 min to 45 min.

[0024] In a preferred embodiment, material A is obtained by uniformly mixing 9.2 to 10.5 parts of acrylic acid and 10 to 15 parts of deionized water.

[0025] In a preferred embodiment, material B is obtained by uniformly mixing 0.2 to 0.4 parts of vitamin C, 1.2 to 1.5 parts of mercaptoethanol and 20 to 25 parts of deionized water.

[0026] In a preferred embodiment, the preparation process of the homemade early strength dispersant is as follows:

[0027] Add an alkaline catalyst to 20-35 parts of triethanolamine, heat to 80-100°C in a nitrogen environment, continuously introduce 1500-2000 parts of ethylene oxide within 210-240 minutes, react for 90-120 minutes, cool to 45-52°C, add 800-900 parts of deionized water, stir for 15-25 minutes, and obtain a self-made early strength dispersant; the alkaline catalyst includes sodium ethoxide.

[0028] In a preferred embodiment, the preparation process of the self-made time-varying fluidity dispersant is as follows:

[0029] Add 320-350 parts of ethoxy vinyl polyether to 400-420 parts of deionized water, add 5-8 parts of hydrophobic slow-release monomer under stirring; add 2.0-2.5 parts of strong oxidant and stir for 5-8 minutes; at the same time, add material C and material D dropwise and react for 40-50 minutes to obtain a self-made time-varying fluidity dispersant.

[0030] In a preferred embodiment, the strong oxidant includes hydrogen peroxide; the hydrophobic slow-release monomer includes octadecyl acrylate; the C material is obtained by uniformly mixing 12 to 15 parts of acrylic acid, 25 to 30 parts of hydroxypropyl acrylate and 50 to 60 parts of deionized water; and the D material is obtained by uniformly mixing 0.3 to 0.6 parts of vitamin C, 0.6 to 1.2 parts of mercaptopropionic acid and 55 to 60 parts of deionized water.

[0031] A method for preparing an admixture for lithium slag concrete comprises the following steps:

[0032] Under stirring conditions, add the homemade super dispersant to the deionized water, stir for 3 to 5 minutes, add the undensified silica fume, stir for 60 to 90 minutes, add the homemade early strength dispersant, the homemade fluidity time-varying dispersant and the liquid triterpenoid saponin in sequence, stir for 30 to 45 minutes, and obtain the lithium slag concrete admixture.

[0033] A concrete contains lithium slag and an admixture for lithium slag concrete. The amount of the admixture for lithium slag concrete added is less than or equal to 2.0% based on the weight of the cementitious material in the concrete.

[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0035] The invention adds a self-made super dispersant, a self-made early strength dispersant, a self-made time-varying fluidity dispersant and a liquid triterpenoid saponin to concrete containing lithium slag; wherein the self-made super dispersant has high-efficiency dispersing performance, thereby reducing the dosage of the lithium slag concrete admixture; the self-made time-varying fluidity dispersant has a strong adsorption effect and molecular effect on cement particles, so that the fluidity of the concrete can be maintained for a certain period of time; the self-made early strength dispersant offsets the slow setting effect caused by excessive dihydrate gypsum, shortens the setting time, and ensures the progress of engineering construction; the liquid triterpenoid saponin contains hydrophilic-hydrophobic groups in its molecular structure, can introduce tiny bubbles into the premixed concrete, thereby exerting a ball effect and making the concrete have good fluidity; that is, the lithium slag concrete admixture of the invention is added during concrete mixing, can improve the difficulty in controlling the dosage of the lithium slag concrete admixture, reduce the production difficulty, can make the lithium slag concrete have good fluidity and workability, meet the requirements of engineering construction, and can also improve the defect of long setting time of concrete, thereby improving the progress of the project. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. The schematic implementation mode of the present invention and its description are only used to explain the present invention and are not intended to limit the present invention. The embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0037] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to those of ordinary skill in the art that these specific details do not have to be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, known structures, materials or methods are not specifically described. The materials, instruments and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. The technical means used in the examples, unless otherwise specified, are conventional means well known to those skilled in the art.

[0038] In order to solve the problems of high admixture dosage, concrete slump loss and long setting time caused by adding lithium slag to concrete, this embodiment provides an admixture for lithium slag concrete, including the following components by weight:

[0039] 80-110 parts of homemade super dispersant, 70-90 parts of homemade early strength dispersant; 40-55 parts of homemade fluidity time-varying dispersant, 20-30 parts of undensified silica fume, 1.0-1.5 parts of liquid triterpenoid saponin, 700-760 parts of deionized water;

[0040] The self-made hyperdispersant is obtained by using a branched polyether monomer as the base material and simultaneously adding material A and material B to react under the action of an initiator, wherein material A is an acrylic acid aqueous solution; material B is an aqueous solution containing vitamin C and mercaptoethanol;

[0041] Among them, the self-made early strength dispersant is obtained by reacting triethanolamine and ethylene oxide as reaction raw materials under the action of alkaline catalyst;

[0042] Among them, the self-made fluidity time-varying dispersant is obtained by using ethoxy vinyl polyether and hydrophobic sustained-release monomer as base materials, and simultaneously adding C material and D material to react under the action of a strong oxidant; wherein, C material is an aqueous solution containing acrylic acid and hydroxypropyl acrylate, and D material is an aqueous solution containing vitamin C and mercaptopropionic acid.

[0043] Among them, the preparation process of the homemade hyperdispersant includes the following steps:

[0044] S1, adding an alkaline catalyst to 50-80 parts of hydroxybutyl vinyl ether, heating to 100-120°C under a nitrogen environment, introducing 980-1020 parts of ethylene oxide within 90-120 minutes, and reacting for 30-45 minutes; adding 31-50 parts of glycidol, reacting for 3-6 minutes, continuously introducing 450-500 parts of ethylene oxide within 120-150 minutes, reacting for 60-80 minutes, cooling to 60°C, and adding 1000-1100 parts of deionized water; obtaining a branched polyether monomer solution; the alkaline catalyst includes KOH; in step S2, the dropwise addition time of material A is 30-40 minutes, and the dropwise addition time of material B is 35-45 minutes.

[0045] S2. Add 50 to 70 parts of deionized water to 200 to 220 parts of branched polyether monomer solution, and control the temperature to 12 to 15°C; add initiator and stir for 5 to 10 minutes, then add material A and material B dropwise at the same time, react for 30 to 40 minutes, and obtain a self-made hyperdispersant; material A is obtained by uniformly mixing 9.2 to 10.5 parts of acrylic acid and 10 to 15 parts of deionized water; material B is obtained by uniformly mixing 0.2 to 0.4 parts of vitamin C, 1.2 to 1.5 parts of mercaptoethanol and 20 to 25 parts of deionized water.

[0046] Among them, the preparation process of the homemade early strength dispersant is as follows:

[0047] Add an alkaline catalyst to 20-35 parts of triethanolamine, heat to 80-100°C in a nitrogen environment, continuously introduce 1500-2000 parts of ethylene oxide within 210-240 minutes, react for 90-120 minutes, cool to 45-52°C, add 800-900 parts of deionized water, stir for 15-25 minutes, and obtain a self-made early strength dispersant; the alkaline catalyst includes sodium ethoxide.

[0048] Among them, the preparation process of the homemade time-varying fluidity dispersant is as follows:

[0049] 320-350 parts of ethoxy vinyl polyether are added to 400-420 parts of deionized water, and 5-8 parts of hydrophobic slow-release monomers are added under stirring conditions; 2.0-2.5 parts of strong oxidants are added and stirred for 5-8 minutes; C material and D material are added dropwise at the same time, and reacted for 40-50 minutes to obtain a self-made fluidity time-varying dispersant. Among them, the strong oxidant includes hydrogen peroxide; the hydrophobic slow-release monomer includes octadecyl acrylate; C material is obtained by uniformly mixing 12-15 parts of acrylic acid, 25-30 parts of hydroxypropyl acrylate and 50-60 parts of deionized water; D material is obtained by uniformly mixing 0.3-0.6 parts of vitamin C, 0.6-1.2 parts of mercaptopropionic acid and 55-60 parts of deionized water.

[0050] The preparation method of the lithium slag concrete admixture comprises the following steps:

[0051] Under stirring conditions, add the homemade super dispersant to the deionized water, stir for 3 to 5 minutes, add the undensified silica fume, stir for 60 to 90 minutes, add the homemade early strength dispersant, the homemade fluidity time-varying dispersant and the liquid triterpenoid saponin in sequence, stir for 30 to 45 minutes, and obtain the lithium slag concrete admixture.

[0052] A concrete contains lithium slag and the above-mentioned lithium slag concrete admixture, and the amount of the lithium slag concrete admixture added is less than or equal to 2.0% based on the weight of the cementitious material in the concrete.

[0053] Embodiment 1:

[0054] An admixture for lithium slag concrete, comprising the following components in parts by weight:

[0055] 80 parts of homemade super dispersant, 70 parts of homemade early strength dispersant; 40 parts of homemade fluidity time-varying dispersant, 20 parts of undensified silica fume, 1.0 part of liquid triterpenoid saponin, and 700 parts of deionized water.

[0056] The preparation process of the above lithium slag concrete admixture is as follows:

[0057] In a 2L three-necked flask, add deionized water, turn on the electric mechanical stirring, stir at medium speed, add the homemade super dispersant, stir for 5 minutes, add the undensified silica fume, stir for 60 minutes, add the homemade early strength dispersant, the homemade fluidity time-varying dispersant, and the liquid triterpene saponin in sequence, stir for 30 minutes, stop stirring, and obtain the lithium slag concrete admixture.

[0058] Among them, the preparation process of the homemade hyperdispersant includes the following steps:

[0059] S1, 50 parts of hydroxybutyl vinyl ether were added to the autoclave, and then 0.05 parts of alkaline catalyst KOH were added, the autoclave cover was covered, nitrogen was introduced for 30 minutes, the addition button was turned on, the temperature in the autoclave was controlled to 100°C, 980 parts of ethylene oxide were introduced continuously within 90 minutes, the reaction was carried out for 30 minutes, 31 parts of glycidol were added, the reaction was carried out for 3 minutes, 450 parts of ethylene oxide were introduced continuously within 120 minutes, the reaction was carried out for 60 minutes, the temperature was lowered to 60°C, 1000 parts of deionized water were added, stirring was started, and stirring was carried out for 20 minutes to obtain a branched polyether monomer solution;

[0060] S2. In a 1L three-necked flask, add 200 parts of branched polyether monomer solution and 50 parts of deionized water, start stirring, and control the temperature to 12°C in an ice-water bath. Prepare dropwise addition liquid A and B, wherein A is obtained by mixing 9.2 parts of acrylic acid and 10 parts of deionized water, and B is obtained by mixing 0.2 parts of vitamin C, 1.2 parts of mercaptoethanol and 20 parts of deionized water. Add 1.2 parts of ammonium persulfate to the three-necked flask, stir for 5 minutes, and drop A and B at the same time. Add A for 30 minutes and B for 35 minutes. Continue to react for 30 minutes, cool to room temperature, and obtain a homemade hyperdispersant.

[0061] Among them, the preparation process of the homemade early strength dispersant is as follows:

[0062] Add 20 parts of triethanolamine into the high-pressure reactor, then add 0.04 parts of alkaline catalyst sodium ethoxide, cover the reactor, pass nitrogen for 35 minutes, turn on the adding button, control the temperature in the reactor to 80°C, pass 1500 parts of ethylene oxide within 210 minutes, react for 90 minutes, cool to 45°C, add 800 parts of deionized water, start stirring, and stir for 15 minutes to obtain a homemade early strength dispersant.

[0063] Among them, the preparation process of the homemade time-varying fluidity dispersant is as follows:

[0064] In a 1L three-necked flask, add 320 parts of ethoxy vinyl polyether (weight average molecular weight of 3000), 400 parts of deionized water, start stirring, add 5 parts of hydrophobic slow-release monomer octadecyl acrylate, and control the temperature to 25°C. Prepare drop-adding liquid C material and D material, wherein C material is obtained by mixing 12 parts of acrylic acid, 25 parts of hydroxypropyl acrylate and 55 parts of deionized water, and D material is obtained by mixing 0.3 parts of vitamin C, 0.6 parts of mercaptopropionic acid and 55 parts of deionized water. Add 2.0 parts of hydrogen peroxide to the three-necked flask, stir for 5 minutes, and add C material and D material at the same time, add C material for 50 minutes, and D material for 60 minutes, continue to react for 40 minutes, cool to room temperature, and change the fluidity to a dispersant.

[0065] Embodiment 2:

[0066] An admixture for lithium slag concrete, comprising the following components in parts by weight:

[0067] 110 parts of homemade super dispersant, 90 parts of homemade early strength dispersant; 55 parts of homemade fluidity time-varying dispersant, 30 parts of undensified silica fume, 1.5 parts of liquid triterpenoid saponin, and 760 parts of deionized water.

[0068] The preparation process of the above-mentioned lithium slag concrete admixture is the same as that of Example 1.

[0069] Among them, the preparation process of the homemade hyperdispersant includes the following steps:

[0070] S1, 80 parts of hydroxybutyl vinyl ether were added to the autoclave, and then 0.1 parts of alkaline catalyst KOH were added, the autoclave cover was covered, nitrogen was introduced for 45 minutes, the addition button was turned on, the temperature in the autoclave was controlled to 120°C, 1020 parts of ethylene oxide were introduced continuously within 120 minutes, the reaction was carried out for 45 minutes, 50 parts of glycidol were added, the reaction was carried out for 6 minutes, 500 parts of ethylene oxide were introduced continuously within 150 minutes, the reaction was carried out for 80 minutes, the temperature was lowered to 60°C, 1100 parts of deionized water were added, stirring was started, and stirring was carried out for 30 minutes to obtain a branched polyether monomer solution;

[0071] S2. In a 1L three-necked flask, add 220 parts of branched polyether monomer solution and 70 parts of deionized water, start stirring, and control the temperature to 15°C in an ice-water bath. Prepare dropwise addition liquid A and B, wherein A is obtained by mixing 10.5 parts of acrylic acid and 15 parts of deionized water, and B is obtained by mixing 0.4 parts of vitamin C, 1.5 parts of mercaptoethanol and 25 parts of deionized water. Add 1.5 parts of ammonium persulfate to the three-necked flask, stir for 10 minutes, and drop A and B at the same time. A is added for 40 minutes, and B is added for 45 minutes. Continue to react for 40 minutes, cool to room temperature, and obtain a homemade hyperdispersant.

[0072] Among them, the preparation process of the homemade early strength dispersant is as follows:

[0073] 35 parts of triethanolamine were added to the high-pressure reactor, and then 0.08 parts of alkaline catalyst sodium ethoxide were added. The reactor cover was closed, nitrogen was introduced for 50 minutes, the adding button was turned on, the temperature in the reactor was controlled to 100°C, 2000 parts of ethylene oxide were introduced continuously for 240 minutes, the reaction was carried out for 120 minutes, the temperature was lowered to 52°C, 900 parts of deionized water were added, stirring was started, and stirring was carried out for 25 minutes to obtain a homemade early strength dispersant.

[0074] Among them, the preparation process of the homemade time-varying fluidity dispersant is as follows:

[0075] In a 1L three-necked flask, add 350 parts of ethoxy vinyl polyether (weight average molecular weight of 3000), 420 parts of deionized water, start stirring, add 8 parts of hydrophobic slow-release monomer octadecyl acrylate, and control the temperature to 30°C. Prepare drop-adding liquid C material and D material, wherein C material is obtained by mixing 15 parts of acrylic acid, 30 parts of hydroxypropyl acrylate and 55 parts of deionized water, and D material is obtained by mixing 0.6 parts of vitamin C, 1.2 parts of mercaptopropionic acid and 60 parts of deionized water. Add 2.5 parts of hydrogen peroxide to the three-necked flask, stir for 8 minutes, and add C material and D material at the same time, add C material for 70 minutes, and D material for 50 minutes, continue to react for 50 minutes, cool to room temperature, and change the fluidity to a dispersant.

[0076] Embodiment 3:

[0077] This embodiment is based on embodiment 1, and the difference from embodiment 1 is that the preparation processes of the homemade super dispersant, homemade early strength dispersant, and homemade fluidity time-varying dispersant are different, specifically:

[0078] Among them, the preparation process of the homemade hyperdispersant includes the following steps:

[0079] S1, 75 parts of hydroxybutyl vinyl ether were added to the autoclave, and then 0.07 parts of alkaline catalyst KOH were added, the autoclave cover was covered, nitrogen was introduced for 40 minutes, the addition button was turned on, the temperature in the autoclave was controlled to 110°C, 1000 parts of ethylene oxide were introduced continuously within 110 minutes, the reaction was carried out for 40 minutes, 40 parts of glycidol were added, the reaction was carried out for 5 minutes, 475 parts of ethylene oxide were introduced continuously within 135 minutes, the reaction was carried out for 70 minutes, the temperature was lowered to 60°C, 1050 parts of deionized water were added, stirring was started, and stirring was carried out for 25 minutes to obtain a branched polyether monomer solution;

[0080] S2. In a 1L three-necked flask, add 210 parts of branched polyether monomer solution and 60 parts of deionized water, start stirring, and control the temperature to 13°C in an ice-water bath. Prepare dropwise addition liquid A material and B material, wherein A material is obtained by mixing 10.0 parts of acrylic acid and 13 parts of deionized water, and B material is obtained by mixing 0.3 parts of vitamin C, 1.4 parts of mercaptoethanol and 23 parts of deionized water. Add 1.4 parts of ammonium persulfate to the three-necked flask, stir for 7 minutes, and drop A material and B material at the same time, drop A material for 35 minutes, drop B material for 40 minutes, continue to react for 35 minutes, cool to room temperature, and obtain a homemade hyperdispersant.

[0081] Among them, the preparation process of the homemade early strength dispersant is as follows:

[0082] Add 30 parts of triethanolamine into the high-pressure reactor, then add 0.06 parts of alkaline catalyst sodium ethoxide, cover the reactor, pass nitrogen for 40 minutes, turn on the adding button, control the temperature in the reactor to 90°C, pass 1800 parts of ethylene oxide within 230 minutes, react for 110 minutes, react for 70 minutes, cool to 50°C, add 850 parts of deionized water, start stirring, and stir for 20 minutes to obtain a homemade early strength dispersant.

[0083] Among them, the preparation process of the homemade time-varying fluidity dispersant is as follows:

[0084] In a 1L three-necked flask, add 300 parts of ethoxy vinyl polyether (weight average molecular weight of 3000), 410 parts of deionized water, start stirring, add 7 parts of hydrophobic slow-release monomer octadecyl acrylate, and control the temperature to 28°C. Prepare drop-adding liquid C material and D material, wherein C material is obtained by mixing 13 parts of acrylic acid, 27 parts of hydroxypropyl acrylate and 52 parts of deionized water, and D material is obtained by mixing 0.4 parts of vitamin C, 0.8 parts of mercaptopropionic acid and 58 parts of deionized water. Add 2.2 parts of hydrogen peroxide to the three-necked flask, stir for 7 minutes, and add C material and D material at the same time, C material is added for 55 minutes, D material is added for 65 minutes, and the reaction is continued for 450 minutes. Cool to room temperature, and the fluidity changes to a dispersant.

[0085] Embodiment 4:

[0086] This embodiment is based on embodiment 1, and the difference from embodiment 1 is that the preparation processes of the homemade super dispersant, homemade early strength dispersant, and homemade fluidity time-varying dispersant are different, specifically:

[0087] Among them, the preparation process of the homemade hyperdispersant includes the following steps:

[0088] S1, 55 parts of hydroxybutyl vinyl ether were added to the autoclave, and then 0.09 parts of alkaline catalyst KOH were added, the autoclave cover was covered, nitrogen was introduced for 36 minutes, the addition button was turned on, the temperature in the autoclave was controlled to 105°C, 1010 parts of ethylene oxide were introduced continuously within 112 minutes, the reaction was carried out for 32 minutes, 48 ​​parts of glycidol were added, the reaction was carried out for 6 minutes, 490 parts of ethylene oxide were introduced continuously within 128 minutes, the reaction was carried out for 72 minutes, the temperature was lowered to 60°C, 1020 parts of deionized water were added, stirring was started, and stirring was carried out for 23 minutes to obtain a branched polyether monomer solution;

[0089] S2. In a 1L three-necked flask, add 218 parts of branched polyether monomer solution and 56 parts of deionized water, start stirring, and control the temperature to 14°C in an ice-water bath. Prepare dropwise addition liquid A and B, wherein A is obtained by mixing 9.6 parts of acrylic acid and 14 parts of deionized water, and B is obtained by mixing 0.2 parts of vitamin C, 1.5 parts of mercaptoethanol and 21 parts of deionized water. Add 1.4 parts of ammonium persulfate to the three-necked flask, stir for 9 minutes, and drop A and B at the same time. A is added for 32 minutes, and B is added for 42 minutes. Continue to react for 36 minutes, cool to room temperature, and obtain a homemade hyperdispersant.

[0090] Among them, the preparation process of the homemade early strength dispersant is as follows:

[0091] Add 25 parts of triethanolamine into the high-pressure reactor, then add 0.08 parts of alkaline catalyst sodium ethoxide, cover the reactor, pass nitrogen for 38 minutes, turn on the adding button, control the temperature in the reactor to 100°C, pass 1900 parts of ethylene oxide within 210 minutes, react for 98 minutes, react for 72 minutes, cool to 46°C, add 830 parts of deionized water, start stirring, stir for 18 minutes, and obtain a homemade early strength dispersant.

[0092] Among them, the preparation process of the homemade time-varying fluidity dispersant is as follows:

[0093] In a 1L three-necked flask, add 330 parts of ethoxy vinyl polyether (weight average molecular weight of 3000), 410 parts of deionized water, start stirring, add 6 parts of hydrophobic slow-release monomer octadecyl acrylate, and control the temperature to 25°C. Prepare drop-adding liquid C material and D material, wherein C material is obtained by mixing 12 parts of acrylic acid, 30 parts of hydroxypropyl acrylate and 54 parts of deionized water, and D material is obtained by mixing 0.4 parts of vitamin C, 0.8 parts of mercaptopropionic acid and 55 parts of deionized water. Add 2.2 parts of hydrogen peroxide to the three-necked flask, stir for 8 minutes, and add C material and D material at the same time, C material is added for 55 minutes, C material and D material are added for 70 minutes, and the reaction is continued for 40 minutes, cooled to room temperature, and the fluidity changes to a dispersant.

[0094] Comparative Example 1:

[0095] This comparative example is based on Example 1, and the difference from Example 1 is that:

[0096] Dispersant in this comparative example: In a 1L three-necked flask, add 100 parts of isopentyl polyoxyethylene ether monomer (Mw is 2400g / mol), 150 parts of deionized water, start stirring, and control the temperature to 12°C in an ice-water bath. Prepare dropwise addition liquid A and material B, wherein material A is obtained by mixing 9.2 parts of acrylic acid and 10 parts of deionized water, and material B is obtained by mixing 0.2 parts of vitamin C, 1.5 parts of mercaptoethanol and 25 parts of deionized water. Add 1.5 parts of ammonium persulfate to the three-necked flask, stir for 5 minutes, and simultaneously add material A and material B, material A is added for 30 minutes, material B is added for 35 minutes, and the reaction is continued for 30 minutes, and cooled to room temperature to obtain a dispersant.

[0097] Comparative Example 2:

[0098] This comparative example is based on Example 1, and differs from Example 1 in that an equal amount of triethanolamine is used to replace the homemade early strength dispersant.

[0099] The admixtures for lithium slag concrete prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 2 were used for C30 concrete testing. Esheng PO 42.5 ordinary silica cement was selected as the cementitious material, the fly ash was Fangyuan II grade ash, and the lithium slag powder was provided by Tianqi Lithium Industry; the artificial machine-made sand was the fine aggregate, and the coarse sand with a fineness modulus of 2.6; the crushed stone was a continuously graded particle size of 5-31.5 mm. The water reducer concrete test was carried out in accordance with GB8076-2016, and the initial slump, expansion and their time-dependent changes, initial setting time, final setting time, 3-day, 7-day strength and 28-day strength and other indicators were tested. The concrete mix ratio is shown in Table 1, and the concrete test results are shown in Table 2:

[0100] Table 1

[0101] cement coal ash Lithium slag powder sand stone water 220 60 50 840 1060 170

[0102] Table 2

[0103]

[0104]

[0105] Note: The lithium slag concrete admixture and PCE are both 1.2% of the cementitious materials in the concrete.

[0106] From the data in Table 2, we can see that:

[0107] 1) When the admixture of the present invention is added to the mixing of lithium slag concrete, the slump and expansion are both within a reasonable range, indicating that the admixture of the present invention can make the lithium slag concrete have good fluidity and workability, meet the requirements of engineering construction, and can also improve the defect of long setting time of concrete, and have higher early strength.

[0108] 2) The self-made early strength dispersant of the present invention can improve the early strength of concrete compared with the existing early strength agent triethanolamine.

[0109] 3) Under the premise of the same amount of admixture, adding homemade hyperdispersant can improve the early strength of concrete compared with not adding it.

[0110] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A lithium slag concrete admixture, characterized in that: It includes the following components by weight: 80-110 parts of homemade super dispersant, 70-90 parts of homemade early strength dispersant; 40-55 parts of homemade fluidity time-varying dispersant, 20-30 parts of undensified silica fume, 1.0-1.5 parts of liquid triterpenoid saponin, 700-760 parts of deionized water; The self-made hyperdispersant is obtained by using a branched polyether monomer as a base material and simultaneously adding material A and material B to react under the action of an initiator, wherein material A is an acrylic acid aqueous solution; material B is an aqueous solution containing vitamin C and mercaptoethanol; The self-made early strength dispersant is obtained by reacting triethanolamine and ethylene oxide as reaction raw materials under the action of an alkaline catalyst; Among them, the self-made fluidity time-varying dispersant is obtained by using ethoxy vinyl polyether and hydrophobic sustained-release monomer as base materials, and simultaneously adding C material and D material to react under the action of a strong oxidant; wherein, the C material is an aqueous solution containing acrylic acid and hydroxypropyl acrylate, and the D material is an aqueous solution containing vitamin C and mercaptopropionic acid.

2. The lithium slag concrete admixture according to claim 1, characterized in that: The preparation process of the self-made hyperdispersant comprises the following steps: S1. Add a basic catalyst to 50-80 parts of hydroxybutyl vinyl ether, heat to 100-120° C. under a nitrogen environment, introduce 980-1020 parts of ethylene oxide within 90-120 minutes, and react for 30-45 minutes; add 31-50 parts of glycidol, react for 3-6 minutes, continuously introduce 450-500 parts of ethylene oxide within 120-150 minutes, react for 60-80 minutes, cool to 60° C., and add 1000-1100 parts of deionized water; obtain a branched polyether monomer solution; S2. Add 50 to 70 parts of deionized water to 200 to 220 parts of the branched polyether monomer solution, and control the temperature to 12 to 15° C.; add the initiator and stir for 5 to 10 minutes, then dropwise add the material A and the material B at the same time, and react for 30 to 40 minutes to obtain the self-made hyperdispersant.

3. A lithium slag concrete admixture according to claim 2, characterized in that: In step S1, the alkaline catalyst includes KOH; in step S2, the dropwise addition time of material A is 30 min to 40 min, and the dropwise addition time of material B is 35 min to 45 min.

4. A lithium slag concrete admixture according to claim 1 or 2, characterized in that: The material A is obtained by uniformly mixing 9.2 to 10.5 parts of acrylic acid and 10 to 15 parts of deionized water.

5. The lithium slag concrete admixture according to claim 1 or 2, characterized in that: The material B is obtained by uniformly mixing 0.2 to 0.4 parts of the vitamin C, 1.2 to 1.5 parts of the mercaptoethanol and 20 to 25 parts of deionized water.

6. The lithium slag concrete admixture according to claim 1, characterized in that: The preparation process of the self-made early strength dispersant is as follows: The alkaline catalyst is added to 20-35 parts of the triethanolamine, the temperature is raised to 80-100° C. in a nitrogen environment, 1500-2000 parts of the ethylene oxide are continuously introduced within 210-240 minutes, the reaction is carried out for 90-120 minutes, the temperature is lowered to 45-52° C., 800-900 parts of deionized water are added, and the mixture is stirred for 15-25 minutes to obtain the self-made early strength dispersant; the alkaline catalyst includes sodium ethoxide.

7. The lithium slag concrete admixture according to claim 1, characterized in that: The preparation process of the self-made time-varying fluidity dispersant is as follows: 320-350 parts of the ethoxy vinyl polyether are added to 400-420 parts of deionized water, and 5-8 parts of the hydrophobic slow-release monomer are added under stirring; 2.0-2.5 parts of the strong oxidant are added and stirred for 5-8 minutes; at the same time, the C material and the D material are added dropwise and reacted for 40-50 minutes to obtain the self-made fluidity time-varying dispersant.

8. The lithium slag concrete admixture according to claim 1 or 7, characterized in that: The strong oxidant includes hydrogen peroxide; the hydrophobic slow-release monomer includes octadecyl acrylate; the C material is obtained by uniformly mixing 12 to 15 parts of the acrylic acid, 25 to 30 parts of the hydroxypropyl acrylate and 50 to 60 parts of deionized water; the D material is obtained by uniformly mixing 0.3 to 0.6 parts of vitamin C, 0.6 to 1.2 parts of mercaptopropionic acid and 55 to 60 parts of deionized water.

9. The method for preparing the lithium slag concrete admixture according to any one of claims 1 to 8, characterized in that: The following steps are involved: Under stirring conditions, the self-made super dispersant is added to deionized water, stirred for 3 to 5 minutes, the undensified silica fume is added, stirred for 60 to 90 minutes, the self-made early strength dispersant, the self-made fluidity time-varying dispersant and the liquid triterpene saponin are added in sequence, stirred for 30 to 45 minutes, and a lithium slag concrete admixture is obtained.

10. A concrete, characterized in that: The concrete contains lithium slag and the lithium slag concrete admixture according to any one of claims 1 to 8, and the amount of the lithium slag concrete admixture added is less than or equal to 2.0% based on the weight of the cementitious material in the concrete.

Citation Information

Patent Citations

  • Alcohol amine early strength agents as well as preparation method and application thereof

    CN106045362A

  • Reinforced cement-based lithium slag grouting material

    CN109369110A

  • Early-strength low-shrinkage concrete for prefabricated parts and preparation process of early-strength low-shrinkage concrete

    CN112794688A

  • Ultrahigh-dispersion type water reducing agent and preparation method thereof

    CN116333231A

  • Solution stopping type polycarboxylate superplasticizer, concrete and preparation method of concrete

    CN117069415A

Cited By

  • Comprehensive recovery method of lithium slag

    CN120714773A

  • Concrete mixing plant

    CN120921518A